Circulating Tumor DNA‐Based Testing and Actionable Findings in Patients with Advanced and Metastatic Pancreatic Adenocarcinoma. (5th March 2021) - Botrus, Gehan; Kosirorek, Heidi; Sonbol, Mohamad Bassam; Kusne, Yael; Uson Junior, Pedro Luiz Serrano; Borad, Mitesh J.; Ahn, Daniel H.; Kasi, Pashtoon M.; Drusbosky, Leylah M.; Dada, Hiba; Surapaneni, Phani Keerthi; Starr, Jason; et al.
Abstract: Purpose: Recent advances in molecular diagnostic technologies allow for the evaluation of solid tumor malignancies through noninvasive blood sampling, including circulating tumor DNA profiling (ctDNA). Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis, often because of late presentation of disease. Diagnosis is often made using endoscopic ultrasound or endoscopic retrograde cholangiopancreatography, which often does not yield enough tissue for next‐generation sequencing. With this study, we sought to characterize the ctDNA genomic alteration landscape in patients with advanced PDAC with a focus on actionable findings. Materials and Methods: From December 2014 through October 2019, 357 samples collected from 282 patients with PDAC at Mayo Clinic underwent ctDNA testing using a clinically available assay. The majority of samples were tested using the 73‐gene panel which includes somatic genomic targets, including complete or critical exon coverage in 30 and 40 genes, respectively, and in some, amplifications, fusions, and indels. Clinical data and outcome variables were available for 165 patients; with 104 patients at initial presentation. Results: All patients included in this study had locally advanced or metastatic PDAC. Samples having at least one alteration, when variants of unknown significance (VUS) were excluded, numbered 266 (75%). After excluding VUS, therapeutically relevant alterations were observed in 170 (48%) of the total 357 cohort, including KRAS (G12C), EGFR, ATM, MYC, BRCA, PIK3CA, and BRAF mutations. KRAS, SMAD, CCND2, or TP53 alterations were seen in higher frequency in patients with advanced disease. Conclusion: Our study is the largest cohort to date that demonstrates the feasibility of ctDNA testing in PDAC. We provide a benchmark landscape upon which the field can continue to grow. Future applications may include use of ctDNA to guide treatment and serial monitoring of ctDNA during disease course to identify novel therapeutic targets for improved prognosis. Implications for Practice: Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis often due to late presentation of disease. Biopsy tissue sampling is invasive and samples are often inadequate, requiring repeated invasive procedures and delays in treatment. Noninvasive methods to identify PDAC early in its course may improve prognosis in PDAC. Using ctDNA, targetable genes can be identified and used for treatment. Abstract : This article characterizes the ctDNA genomic alteration landscape in patients with advanced pancreatic ductal adenocarcinoma, with a focus on actionable findings.